Detection of (pslA, and PA-SS) Genes in Pseudomonas aeruginosa Isolated from Clinical Cases - Fouad Raouf Raouf , Tara; Dölarslan, Melda; Mujahid Abdullah, Rana (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In the current study, 100 different clinical samples were collected in Baghdad hospitals, including Teaching Laboratories Hospital, Medical City, Baghdad Teaching Hospital, and Martyr Ghazi Hariri Hospital, for a period from May 2022 to September 2022. After diagnosis, we obtained 19 isolates of Pseudomonas aeruginosa from different clinical sources, including burns, wounds, urinary tract infections, otitis media, and blood. Cultured all samples on MacConkey, cetrimide agar. Then it underwent several microscopic and biochemical tests. Included are: Oxidase, Citrate utilization, Triple sugar-iron (TSI), catalase, Gelatinase, Motility and Ornithine decarboxylation tests. Pseudomonas aeruginosa susceptibility to 11 antibiotics was tested using the disc diffusion method. It has been shown that Pseudomonas aeruginosa has multi-antibiotic resistance. It showed that all isolates were resistant to Penicillin 98%, Cefuroxime Sodium 98%, Amoxicillin/clavulanic Acid 98%, Erythromycin 98%, Oxacillin 98%, Cefotaxime 76%, Ofloxacin 58%, Cefipime 22%, Ceftazidime 16%, and Imipenem 16%. Amikacin was the most effective in isolates, as it was found that 8% are resistant to it. The bacteria's ability to produce biofilm was assessed using a crystal violet (CV) assay, and it was found that all isolates by 100% had the ability to produce biofilm. 15 isolates were  84% strong-forming, 2 (8%) were moderate-forming, and 2 (8%) were weak-biofilm-forming. The biofilm genes pslA, and PA-SS were studied. The results of this study showed that all isolates of Pseudomonas aeruginosa possess these genes by 100%.